Towards a more inclusive child and adolescent mental health research: Bridging gaps through neuro‐affirmative, transdiagnostic, and participatory frameworks - Alessio Bellato; Asilay Seker (JCPP Advances)
Abstract The field of child and adolescent mental health research is currently undergoing important shifts. In line with its mission to support accessible child mental health science for all, JCPP Advances has included 12 studies in its June 2025 issue, eight of which are presented in this editorial. These articles reflect how recent changes are influencing research in the field. These include the adoption of transdiagnostic frameworks to better understand shared mechanisms across diagnostic categories, and the growing use of participatory research to involve children, young people, and families in the design of assessments and interventions. The highlighted papers examine emotion regulation in autism, longitudinal pathways to psychopathology, the role of family dynamics and prosocial behaviours, and the development of accessible, inclusive tools and interventions. Together, they showcase how the field is evolving to become more developmentally informed, inclusive, and responsive to the real‐world needs of young people and their support networks.